Analisis Sensori dan Kimia Stik Substitusi Tepung Kacang Hijau dengan Penambahan Rempah Temu Kunci - Agustina, Sri; Kurniawan, Muhammad fakih; Nurhalimah, Siti (Jurnal Pangan dan Gizi, 2024)
Stick is a snack that is often consumed. Fingerroot is an Indonesian herbal plant that has a relatively strong taste and aroma. The use of fingerrot as a food ingredient is not optimal due to of its pungent aroma and bitter taste. The research objective was to utilize key fingerrot flour in the manufacture of stick products to add flavor and aroma. The research method applied was Completely Randomized Design (CRD) with five treatment levels, namely the addition of fingerroot flour by 0% (control), 1%, 2%, 3% and 4%. Stick analysis included sensory quality, hedonic, chemical quality, statistic analyzed, selected products were subjected to protein analysis, ash content, carbohydrates and caloric value. The high concentration of fingerroot flour added resulted in the color of the stick towards dark brown, the aroma towards the aroma of fingerroots, the taste towards the taste of fingerroots, and the aftertaste towards the bitter taste of fingerroots making the level of preference for the fingerroot sticks. lower. The sticks with the best treatment had 3,14% moisture content, 28,90% fat content, 0,10% ash content, 3,90% protein content, 63,97% carbohydrates and 532.52 kcal calories.